Organizational models of cancer patient routing at the regional level - Sergey A. Parts; Igor V. Reshetov; Evgeniya S. Kuzmina; Vsevolod N. Galkin (ZAO "Consilium Medicum", 2023)
The main objective of the oncology patient routing system in the region is to ensure the accessibility and quality of outpatient oncology care. According to the regulatory documents of the Ministry of Health of Russia, the key role in the routing system is assigned to outpatient cancer care centers. We analyzed the regulatory requirements for the operation of the centers and proposed algorithms for their integration in the regions. Based on the developed algorithms, routing modeling and a rank assessment of the models were performed with a subsequent risk assessment and rationale for organizational measures to mitigate the risks.